Candide-Cofor et la prévision de besoins en main-d’oeuvre par occupation et par industrie au Canada / Forecasting Manpower needs by Occupation and Industry in Canada - Proulx, Pierre-Paul; Bourgault, Luce; Manegre, Jean-François (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
The authors present a review and an assessment of the Candide1and Cofor2models as instruments for estimating manpower requirements at the industry and provincial levels. In summary form the approach is as follows. Following upon a forecast of Real Domestic Product by industry generated by Candide, Cofor allows the preparation of estimates of total employment by industry at the national level by making use of productivity equations of the following form: In Y/L = f (T) where Y is Real Domestic Product, L is employment and T is a time trend. In certain instances K (capital stock) is used instead of T. Then total employment by industry is estimated at the provincial level by extrapolating the ratio of total employment in the industry by province to that at the national level. Finally employment by occupation is obtained by applying the 1971 Census occupational distribution of experienced labour force by industry at the provincial level. Adjustments are made for death and retirement rates as observed at the all industry and Canada levels.The paper then illustrates the use of the models with results obtained for the Canadian industrial chemicals and Québec textiles and total Québec industries.Comments are then made concerning the strenght and weaknesses of the models. Among these are:1) The use of average productivity estimates to examine manpower requirements in industries contemplating large scale projects.2) An implicit hypothesis to the effect that capacity is utilized fully.3) The aging of the occupational distributions, and the use of experienced labour force rather than employment in the analysis of occupational distributions.4) Estimates for both sexes together rather than by sex.5) Lack of adjustments to reflect the age-experience profiles by industry.6) Lack of adjustment for recent significant increases in turnover rates.7) Insufficient adjustment for cyclical effects.8) Inadequate disaggregation at the provincial level, etc..1 Canadian Disaggregated Interdepartmental Econometric Model operated by the Economic Council of Canada.2 Canadian Occupational Forecasting Model developed and operated by the Canadian Department of Manpower and Immigration.